The role of tissue culture in the establishment of disease free germplasm for international distribution - Ng, S.Y.C.; Rossel, H.W.; Thottappilly, G. (1990)
Meristem-tip culture is being used to eliminate viruses from plants. The fact that some viruses are easier to eliminate than others has been utilized in thermotherapy and chemotherapy, along with meristem-tip culture, to increase the efficacy of disease elimination. Tissue culture materials are considered the most suitable form for international exchange of vegetative plant materials and the method is well accepted by national quarantine authorities. Clonal germplasm of cassava and sweet potato has been distributed in this form by IITA to many countries in Africa and elsewhere. This has greatly contributed to the improvement of these root and tuber crops in many countries through testing, selection and eventual release of new, high-yielding, disease and pest resistant varieties.